A Novel Predictor of Posttransplant Portal Hypertension in Adult-To-Adult Living Donor Liver Transplantation: Increased Estimated Spleen/Graft Volume Ratio. Issue 10 (October 2016) - Gyoten, Kazuyuki; Mizuno, Shugo; Kato, Hiroyuki; Murata, Yasuhiro; Tanemura, Akihiro; Azumi, Yoshinori; Kuriyama, Naohisa; Kishiwada, Masashi; Usui, Masanobu; Sakurai, Hiroyuki; Isaji, Shuji
Abstract : Background: In adult living donor liver transplantation (ALDLT), graft-to-recipient weight ratio of less than 0.8 is incomplete for predicting portal hypertension (>20 mm Hg) after reperfusion. We aimed to identify preoperative factors contributing to portal venous pressure (PVP) after reperfusion and to predict portal hypertension, focusing on spleen volume-to-graft volume ratio (SVGVR). Methods: In 73 recipients with ALDLT between 2002 and 2013, first we analyzed survival according to PVP of 20 mm Hg as the threshold, evaluating the efficacy of splenectomy. Second, we evaluated various preoperative factors contributing to portal hypertension after reperfusion. Results: All of the recipients with PVP greater than 20 mm Hg (n = 19) underwent PVP modulation by splenectomy, and their overall survival was favorable compared with 54 recipients who did not need splenectomy (PVP ⩽ 20 mm Hg). Graft-to-recipient weight ratio had no correlation with PVP. Multivariate analysis revealed that estimated graft and spleen volume were significant factors contributing to PVP after reperfusion ( P < 0.0001 and P < 0.0001, respectively). Furthermore, estimated SVGVR showed a significant negative correlation to PVP after reperfusion ( R = 0.652), and the best cutoff value for portal hypertension was 0.95. Conclusions: In ALDLT, preoperative assessment of SVGVR is a good predictor of portal hypertension after reperfusion can be used to indicate the need for splenectomy before reperfusion. Abstract : The investigators identify spleen/graft volume ratio as a predictor of posttransplant portal hypertension in living donor liver transplantation. This metric is proposed for guiding portal modulation in the prevention of small-for-size syndrome.